Differential Glycosylation Expression in Injured Rat Spinal Cord Treated with Immunosuppressive Drug Cyclosporin-A - Kilcoyne, Michelle (ACS Omega, 2019)
[Image: see text] Glycosylation is ubiquitous throughout the central nervous system and altered following spinal cord injury (SCI). The glial scar that forms following SCI is composed of several chondroitin sulfate proteoglycans, which inhibit axonal regrowth. Cyclosporin-A (CsA), an immunosuppressive therapeutic, has been proposed as a potential treatment after SCI. We investigated CsA treatment in the spinal cord of healthy, contusion injured, and injured CsA-treated rats. Lectin histochemistry using fluorescently labeled lectins, SBA, MAA, SNA-I, and WFA, was performed to identify the terminal carbohydrate residues of glycoconjugates within the spinal cord. SBA staining decreased in gray and white matter following spinal cord injury, whereas staining was increased at the lesion site in CsA-treated animals, indicating an increase in galactose and N-acetylgalactosamine terminal structures. No significant changes in MAA were observed. WFA staining was abundant in gray matter and observed to increase at the lesion site, in agreement with increased expression of chondroitin sulfate proteoglycans. SNA-I-stained blood vessels in all spinal cord regions and dual staining identified a subpopulation of astrocytes in the lesion site, which expressed α-(2,6)-sialic acid. Glycosylation were altered in injured spinal cord treated with CsA, indicating that glycosylation and alteration of particular carbohydrate structures are important factors to consider in the examination of the environment of the spinal cord after injury.